(untitled) - Rosemary Border (Oxford, 1998)
The Earth is disappeared under a mountain of rubbish - often poisonous - yet, as this book shows, much of this rubbish could be recycled. Recycling can save energy, materials and money - it may also save the Earth.
Keywords: almanacs,curiosities and wonders